Penerapan Mobilisasi Progresif Level 1 terhadap Saturasi Oksigen - Razita Sima Mentari; Fitriyati Fitriyati (Lembaga Pengembangan Kinerja Dosen, 2026)
Critically ill patients treated in the Intensive Care Unit (ICU) often experience prolonged immobilization, which can affect the stability of their oxygen saturation status. One nursing intervention that can be performed to help maintain the stability of the patient's condition is level I progressive mobilization. This study aims to determine the effect of level I progressive mobilization on the oxygen saturation status of critically ill patients. The method used was a literature review by examining several scientific articles using the PRISMA method obtained from databases such as PubMed, Google Scholar, J-Stage, SpringerLink, and ResearchGate for the period 2019-2025. The selected journal articles were studies related to progressive mobilization in critically ill patients in the ICU. Various research articles showed that level I progressive mobilization had a positive impact on patients' oxygen saturation status. Discussion: several studies reported an increase or stabilization in oxygen saturation, blood pressure, heart rate, and respiratory rate after mobilization. Level I progressive mobilization can be one of the nursing interventions that support the stability of critical patients in the ICU. Further research is still needed to strengthen the scientific evidence regarding the effectiveness of this intervention.